Try this option:
the rule: if f(-x)=f(x), then the function f(x) is even, if f(-x)=-f(x) then the function is odd.
1. f(x)=-5x⁴-2;
if to substitute x→(-x), then f(-x)=-5*(-x)⁴-2; ⇔ f(-x)=-5x⁴-2, in other words f(x)=f(-x), it means that this function is even.
2. f(x)=x³+2x.
if to substitute x→(-x), then f(-x)=(-x)³+2*(-x); ⇔ f(-x)=-(x³+2x), in other words f(-x)=-f(x), it means that this function is odd.
-3 > x
The values that make this inequality true are those that are less than -3. The inequality does not include -3.
Answer:
Their are no possible factors for this expression.
Step-by-step explanation:
A = bh
b = 7 + 4 = 11
h = 8
11(8) = 88
The correct answer is B. 88 m^2